New approach to implement cancer patient care: The valutazione percorso rete oncologica campana (ValPeROC)‐experience from an Italian oncology network. (25th October 2022) - Crispo, Anna; Rivieccio, Giorgia; Cataldo, Luca; Coluccia, Sergio; Luongo, Assunta; Coppola, Elisabetta; Grimaldi, Maria; Montagnese, Concetta; Nocerino, Flavia; D'Errico, Davide; Celentano, Egidio; Saviano, Rocco; et al.
Abstract: Objective: The primary goal of the Campania Oncology Network (ROC) was to reduce cancer delay and care fragmentation through the establishment of cancer‐specific multidisciplinary oncologic groups (GOMs) and diagnostic and therapeutic assistance paths (PDTAs). Methods: Five cancer centres of the ROC, with their own cancer specific GOM, were selected. In our analysis, we have focused on four neoplasms: lung, colon, ovarian and prostate cancers. The median time for pre‐GOM and GOM Times was calculated for each tumour site. Univariate and multivariate logistic regressions were performed to individuate risk factors for pre‐GOM and GOM Time. Results: Significant differences were observed for prostate cancer compared to other patients either for pre‐GOM or GOM Times. Significant risks were found for ovarian and prostate cancers in pre‐GOM time and for prostate cancer in GOM‐Time. Conclusions: This experience will produce knowledge and data to guide decision‐making and to manage more effectively the challenges of fighting cancer in Campania region. The Valutazione Percorso Rete Oncologica Campana (ValPeROC) study evaluates, for the first time, the ROC activity, through the analysis of key performance indices. Pre‐GOM and GOM Time represent the quality of the entire regional health system and are useful to define models, which can evaluate the performance of the ROC over time.